AromaSens - Ali Yeon, Md Shakaff, Prof. Dr.; Abd Hamid, Adom, Assoc. Prof. Dr.; Mohd Noor, Ahmad, Prof. Dr. (Malaysian Invention & Design Society (MINDS), 2010)
Prof. Dr. Ali Yeon and his team won silver for AromaSens. ITEX 2005, 19th - 21st May 2005 was held at Putra World Trade Centre (PWTC), Kuala Lumpur.